Uji Validitas Metode Imunokromatografi Test Dengan Metode Mikroskopis Pada Infeksi Malaria Falciparum - Muhammad Jupri; Suharsih Thahir; Muhammad R izman Naim (Jurnal Media Laboran, 2018)
Malaria is one of the public health problems in Indonesia. Although malaria morbidity and mortality rates in Indonesia currently tend to decline, however, the government views malaria as still a threat to public health status, especially for poor people living in remote areas. In malaria endemic areas where malaria morbidity is still very high. Malaria diagnosis can be established by microscopic examination which is a standard Gold examination. In addition, Tets or Rapid Test immunochromatography can also be used as an alternative examination. Research has been conducted to compare the Microscopic method and the Immunochromatography Test method for malaria testing. This study aims to determine the sensitivity, specificity, positive predictive value, negative predictive value of malaria examination method Immunochromatography Test. The study was conducted at the Lacasino medical Center Clinical Laboratory, as many as 20 samples from patients suspected of malaria and obtained 8 positive samples Immunocromatography Test method and Microscopic method, 5 negative samples with Immunocromatography Test method and Microscopic method, 4 samples microscopic negative method and 3 negative sample methods Immunochromatography Test. The diagnostic test showed a sensitivity of 84%, a specificity of 55%, a positive predictive value of 21% and a negative predictive value of 29%, so that the method of Imunochromatography Test could be used as a filter test or screening test.